Impact of Previous Pulmonary Tuberculosis on Lung Function and Risk of Developing Asthma-Like Airway Obstruction - Sajjad Ali, Muhammad Sohrab Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pulmonary tuberculosis (PTB) causes permanent structural and inflammatory alterations in the airways that can start to persist even after microbiological treatment. Persistent respiratory symptoms and spirometry abnormalities appear in many patients, and the scope of the asthma-type airway blockage following PTB is not adequately defined in the tuberculosis-stricken countries. Objective: To evaluate the effect of prior pulmonary tuberculosis on lung function, and to estimate the prevalence of asthma-like airway-blocking in adults with a history of treated PTB. Methodology: It is a cross-sectional comparative study that was carried out at the department of Pulmonology of a MTI-Mardan Medical Complex, Mardan between November 2022 and April 2023. Two hundred adults who had documented and successfully treated PTB (>6 months later) were recruited and compared to 200 age- and sex-matched controls who had never had any history of PTB before. Standardised respiratory questionnaires were performed for all subjects, and pre- and post-bronchodilator spirometry was done as per the ATS/ERS guidelines. Post-bronchodilator FEV 1/FVC with the definition of airway obstruction less than 0.70. Airflow obstruction with a high bronchodilator reversibility (i.e. ΔFEV 1 3) was considered asthma-like airway obstruction. SPSS version 24.0 was used to analyses the data. Results: The PTB group had a mean age of 45.6 ± 12.8 years, while controls had a mean age of 44.2 ± 11.9 years (p = 0.41). Mean post-bronchodilator FEV₁% predicted was significantly lower in post-TB patients (68.3 ± 15.7) than in controls (82.9 ± 13.4; p < 0.001). Airway obstruction was observed in 38.3% of PTB patients compared with 15.0% of controls (p < 0.001). Asthma-like airway obstruction was present in 20.0% of PTB patients versus 6.7% of controls (p = 0.002). Conclusion: Repeated pulmonary tuberculosis is related to considerable long-term dysfunction of the lungs and a greatly enhanced likelihood of airway hindrance characteristic of asthma. Post-TB spirometry surveillance can be conducted regularly to allow detection and treatment of reversible airflow limitation at an earlier stage in this at-risk group. Keywords: Pulmonary tuberculosis; Lung function; Airway obstruction; Asthma-like disease